Analysis of D216H Polymorphism in Argentinean Patients With Primary Dystonia. (June 2013) - Caputo, Mariela; Irisarri, Maximiliano; Perandones, Claudia; Alechine, Evguenia; Pellene, Luis Alejandro; Roca, Claudia Uribe; Micheli, Federico E.; Corach, Daniel
Abstract The D216H polymorphism (rs1801968) in TOR1A has been suggested as a risk factor for developing primary dystonia in German subjects not carrying the deletion c.904-906delGAG (∆GAG). However, this association could not be confirmed in other populations with different ethnic backgrounds. The purpose of this study is to evaluate the D216H polymorphism in an Argentinean cohort of 40 patients with primary dystonia and 200 unrelated control subjects. The authors could observe a significantly higher frequency of the H216 variant in dystonic patients lacking ∆GAG as compared with controls.